HUBUNGAN STATUS GIZI TERHADAP MALOKLUSI (Literature Review) - Melan Anisa; Diana Wibowo; Riky Hamdani (Dentin, 2022)
ABSTRACT Background: Indonesia’s still has many health problems, two of them is undernutrition and overnutrition. The population of South Kalimantan has a prevalence of 15.1% underweight, 15% overweight, and 15.4% obese. Nutritional status can affect growth and development of children's teeth and jaws, which can cause malocclusion. Crowded teeth are the most common type of malocclusion, and it’s experienced by almost 2/3 of the human population. Purpose: The purpose of this literature review is to analyze the relationship between nutritional status and malocclusion in the relevant literature in the last 10 years. Method: This study uses literature review method with a narrative review procedure, which focuses on describe and explain the topic, and contains sources that are appropriate to the topic. All reviewed articles were obtained from searching at Pubmed, Science Direct, and Google Scholar data sources. Results: The highest prevalence of nutritional status was normal with a percentage of 60.1%. The prevalence of malocclusion is higher (65.70%) compared to normal occlusion (43.30%). The most common type of crowding is light crowding. The majority of literature states that there is a relationship between nutritional status and malocclusion. Conclusion: People are expected to take advantage from the results of this study as a reference so they pay more attention to a balanced nutritional intake and maintain their oral health. Keywords: Crowding teeth, Malocclusion, Nutritional statusABSTRAKLatar Belakang: Kondisi kesehatan masyarakat Indonesia masih memiliki banyak masalah dan salah satunya adalah gizi kurang dan gizi berlebih. Penduduk Kalimantan Selatan memiliki prevalensi berat badan kurus sebesar 15,1%, berat badan lebih 15%, dan obesitas 15,4%. Status gizi berpengaruh pada tumbuh kembang gigi dan rahang anak sehingga dapat mengakibatkan maloklusi. Gigi berjejal merupakan jenis maloklusi yang paling sering terjadi, bahkan kasus ini dialami hampir 2/3 populasi manusia. Tujuan: Tujuan literature review ini untuk menganalisis hubungan antara status gizi terhadap maloklusi pada literatur yang relevan 10 tahun terakhir. Metode: Penelitian menggunakan metode literature review dengan prosedur narrative review, yaitu melakukan penguraian dan penjelasan yang berfokus pada topik, dan memuat sumber-sumber yang sesuai topik tersebut. Semua artikel yang direview diperoleh dari pencarian sumber data Pubmed, Science Direct, dan Google Scholar. Hasil: Prevalensi Status gizi terbanyak adalah gizi normal sebanyak dengan persentase sebanyak 60,1%. Prevalensi maloklusi memiliki jumlah yang lebih banyak yaitu sebesar 65,70% dibandingkan oklusi normal yang hanya sebesar 43,30%. Hasil pengukuran maloklusi tipe gigi terbanyak adalah gigi berjejal ringan. Mayoritas literatur menyatakan terdapat hubungan antara status gizi terhadap maloklusi. Kesimpulan: Masyarakat diharapkan dapat memanfaatkan hasil penelitian ini acuan agar lebih memperhatikan asupan gizi yang seimbang dan menjaga kesehatan rongga mulutnya.Kata Kunci: Gigi berjejal, maloklusi, status gizi